Search, Action, and Share: The Online Behaviour Relating to Mobile Instant Messaging App in the Tourism Context - SUHUD, Usep; ALLAN, Mamoon (Journal of Environmental Management and Tourism; Vol 11 No 4 (2020): JEMT Volume XI Issue 4(44) Summer 2020DO - 10.14505//jemt.11.4(44).14, 2020)
This study aims to assess the AISAS (attention – interest – search – action – share) model in a tourism setting. AISAS is considered as the most comprehensive model to illustrate one’s behaviour relating to modern media, particularly mobile instant messaging application. So far, the studies on AISAS in the tourism context are limited. Participants of this study were those who had a mobile instant messaging app, member of a chat group and had an experience holidaying after obtaining information from other group members and sharing their holidaying expertise in the same chat group. Data were collected by using an online instrument and attracted 408 participants consisting of 132 males and 276 females. This study found that the AISAS model can predict tourists’ behavioural relating to the use of mobile instant messengers as a medium for searching and sharing information. This study showed how tourists became a ‘cyborg’ when they attached to the internet of thing (IoT) in every stage of their behaviour relating to tourism activities.